A laser interference/high-speed photography method for the study of triple phase contact-line movements and lateral rewetting flow during single bubble growth on a small hydrophilic heated surface. (January 2019) - Liu, Jing-nan; Gao, Ming; Zhang, Ling-shuang; Zhang, Li-xin
Abstract: The laser interferometric method and high-speed camera techniques are used simultaneously to study dynamic characteristics of a single vapor bubble growth and departure from an ITO heater surface submerged in ethanol. Two high-speed cameras are used simultaneously in this experiment: one is used to record interference fringes of the microlayer at the bubble's bottom and the other is used to record the growth and detachment of the single bubble synchronously from the side view. By comparing these images frame by frame, it is found that the bubble's growth time can be divided into two periods sequentially: the microlayer period and the lateral rewetting period. Variations of dry spot radius, bubble contact radius, bubble volume and diameter, dynamic contact angles during these two periods are illustrated.